2022
DOI: 10.1039/d2dt00401a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of halogenation of salicylaldehyde on the antiproliferative activities of {Δ/Λ-[Ru(bpy)2(X,Y-sal)]BF4} complexes

Abstract: Ru(II) polypyridyl complexes are widely used in biological fields, due to physico- chemical and photophysical properties. In this paper, a series of new chiral Ru(II) polypyridyl complexes (1-5) with general...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 76 publications
2
21
0
Order By: Relevance
“…We also synthesized a new set of chiral Ru(II) polypyridyl complexes, namely Δ/Λ-[Ru(bpy) 2 (X,Y-Sal)]BF 4 , where X,Y-Sal is halogenated salicylaldehyde with chloride and/or bromide substitutions in 3 and 5 positions. 22 We also found that the type, number, and position of the halogen substituents are important factors in determining the cytotoxicity of these compounds. removed under vacuum providing a solid which was dissolved in the minimum amount of chloroform and precipitated with n-hexane.…”
Section: ■ Introductionmentioning
confidence: 79%
“…We also synthesized a new set of chiral Ru(II) polypyridyl complexes, namely Δ/Λ-[Ru(bpy) 2 (X,Y-Sal)]BF 4 , where X,Y-Sal is halogenated salicylaldehyde with chloride and/or bromide substitutions in 3 and 5 positions. 22 We also found that the type, number, and position of the halogen substituents are important factors in determining the cytotoxicity of these compounds. removed under vacuum providing a solid which was dissolved in the minimum amount of chloroform and precipitated with n-hexane.…”
Section: ■ Introductionmentioning
confidence: 79%
“…The selected suitable crystal was mounted using polybutene oil on a flexible loop fixed on a goniometer head and immediately transferred to the diffractometer. Pre‐experiment, data collection, data reduction, and analytical absorption correction [37] were performed with the program suite CrysAlisPro [38] . Using Olex2 , [39] the structure was solved with the SHELXT [40] small molecule structure solution program and refined with the SHELXL2018/3 program package [41] by full‐matrix least‐squares minimization on F [38] .…”
Section: Methodsmentioning
confidence: 99%
“…Pre-experiment, data collection, data reduction, and analytical absorption correction [37] were performed with the program suite CrysAlisPro. [38] Using Olex2, [39] the structure was solved with the SHELXT [40] small molecule structure solution program and refined with the SHELXL2018/3 program package [41] by full-matrix least-squares minimization on F. [38] PLATON [42] was used to check the result of the X-ray analysis. Deposition Number 2269280 contains the supplementary crystallographic data for this paper.…”
Section: X-ray Diffraction Studymentioning
confidence: 99%
“…Additionally, the 1205Lu melanoma cells were used to test anticancer activity for 72 h. After this study, DW1 was found to be more potent than DW2 against protein kinase inhibitors [57]. A series of new chiral Ru(II) polypyridyl complexes (1-5) with the general formula {Δ/Λ-[Ru(bpy)2(X,Ysal)]BF4} (bpy = 2,2′-Bipyridyl; X,Y-sal = 5-bromosalicyl aldehyde (1), 3,5-dibromosalicylaldehyde (2), 5-chlorosalicyl aldehyde (3), 3,5-dichlorosalicylaldehyde (4) and 3-bromo-5chlorosalicylaldehy (5) were also synthesized [58]. Subsequently, the anticancer activities of all synthesized complexes were tested against human lung cell lines (A549).…”
Section: Chiral Complex Of Rutheniummentioning
confidence: 99%
“…Subsequently, the anticancer activities of all synthesized complexes were tested against human lung cell lines (A549). Among all synthesized compounds, only three complex compounds (1, 2 and 5) were found as active drugs because they were showing the highest anticancer activity against the taken cell lines [58].…”
Section: Chiral Complex Of Rutheniummentioning
confidence: 99%